"Remember me, will you?": Overusing material gifts for interpersonal memory management. Issue 4 (13th December 2021) - Yang, Adelle X.; Koo, Minjung; Hwang, Jaewon
Abstract: Six experiments ( N = 2350) uncover a prevalent giver–recipient preference discrepancy: gift givers prefer giving material gifts (vs. experiential gifts) more than gift recipients prefer to receive them. The experiments reveal congruent evidence that a mnemonic gifting strategy underlies this preference discrepancy. Givers are more likely than recipients to consider the memory consequences of gift options, as givers intuitively use material gifts as interpersonal mnemonic devices to facilitate the recipient's retrieval of giver‐related memories. As such, this preference discrepancy occurs in various stages of developing relationships but is mitigated in very close relationships. In addition, two theoretical moderators are identified: The preference discrepancy disappears when the gift would be associated with an unpleasant occasion (instead of a pleasant one), and when the giver and recipient expect an incidental increase in future interactions. This research reveals an interpersonal memory management motive that underlies the miscalibrated gift choices, and bridges prior findings on material and experiential gifts. These findings also offer insights for consumers and marketers to mitigate miscalibrated choices and their perverse economic and relationship consequences.